A conversation with Ernesto Mulato : the political and military struggle in Angola - American Enterprise Institute for Public Policy Research (Washington : The Institute, 1979)
This book presents the edited transcript of a meeting held at the American Enterprise Institute with a leading member of the political bureau of Angola's UNITA party. The book describes and evaluate the current situation in Angola and its implications for the rest of Africa.
Includes bibliographical references
ahz 12/03/2019
Loans
Keywords: National liberation movements; Angola